A policy analysis of the EU Emissions Trading System and its crisis - Julia Anna Ruf (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2017)
This paper provides a policy analysis of the EU Emissions Trading System and its crisis. The aim of the research is to give an answer to the question why the EU Emissions Trading System is in crisis and cannot be revised in an effective way. Therefore, the policy process of the revision of the EU Emissions Trading System for its third phase is analysed. The research is based on the theoretical assumptions of the historical-materialist policy analysis, which also serves as an analytical tool. The main result of the analysis is that the framing of neoliberalism has shaped the construction and the further revisions of the system. For this reason, the EU Emissions Trading System can be considered to be in crisis because it is based on neoclassical assumptions, which are not suitable for tackling the issue of climate change. Revisions will not lead to a success of the system as long as it is based on neoclassical economics. However, the current strength of neoliberalism makes a turning away unlikely.
Keywords: O13; Q48; Q54; Q58; 330; EU Emissions Trading System; Crisis; Revision; Neoliberalism; Historical-Materialist Policy Analysis